Independent Association of Overhydration with All-Cause and Cardiovascular Mortality Adjusted for Global Left Ventricular Longitudinal Systolic Strain and E/E' Ratio in Maintenance Hemodialysis Patients - Jiun-Chi Huang; Yi-Chun Tsai; Pei-Yu Wu; Jia-Jung Lee; Szu-Chia Chen; Yi-Wen Chiu; Ya-Ling Hsu; Jer-Ming Chang; Hung-Chun Chen (Karger Publishers, 2018)
Background/Aims: Fluid overload is common and associated with morbidity and mortality in patients with end-stage renal disease. The relationship between fluid overload and cardiac function is complex, and whether fluid overload is associated with adverse outcomes in patients undergoing hemodialysis (HD) independently of systolic and diastolic function of the left ventricle (LV) remains unclear. Methods: The present study aimed to investigate the relationship between overhydration and all-cause and cardiovascular (CV) mortality after adjusting for LV function in 178 maintenance HD patients. The relative hydration status (overhydration/ extracellular water, ∆HS) was measured using a body composition monitor, and then used to assess the fluid status. A ∆HS ≥7% was defined as fluid overload. Global left ventricular longitudinal systolic strain (GLS), and the early filling and early diastolic mitral annular velocity (E/E') ratio were assessed using speckle-tracking and tissue Doppler echocardiography. Results: During a mean follow-up period of 2.7 years, 24 patients died, including 11 CV deaths. An increased ∆HS was significantly associated with all-cause and CV mortality in the univariate analysis. This prognostic significance remains after multivariate adjusting for GLS and E/E' ratio for all-cause (HR, 1.123; 95% CI, 1.063-1.186; p-value < 0.001) and CV (HR, 1.088; 95% CI, 1.005-1.178; p-value =0.037) mortality. Moreover, ∆HS significantly improved the prognostic value beyond conventional clinical and echocardiographic parameters. Conclusion: A higher ∆HS was independently associated with increased all-cause and CV mortality after adjusting for systolic and diastolic function of the LV. This suggests that ∆HS may be a relevant target for improving outcomes in maintenance HD patients.